Characteristics, formation and evolution of pre-salt dolomite reservoirs in the fifth member of the Ordovician Majiagou Formation, mid-east Ordos Basin, NW China - FU, Siyi; ZHANG, Chenggong; CHEN, Hongde; CHEN, Anqing; ZHAO, Junxing; SU, Zhongtang; YANG, Shuai; WANG, Guo; MI, Wentian (Petroleum exploration and development, 2019)
The characteristics and formation of the pre-salt dolomite reservoirs in the fifth member of Ordovician Majiagou Formation in the mid-east Ordos Basin are investigated through observation of cores and thin sections, and geochemical analysis. (1) The pre-salt dolomites can be divided into dolomicrite, grain dolomite and dolarenite, in which the main reservoir space consists of intercrystalline pores and various dissolved pores. (2) The diagenesis in the study area is complex and mainly includes dolomitization, dissolution, filling, and recrystallization. (3) Multi-stages of dolomitization, including penecontemporaneous capillary concentration dolomitization, seepage-reflux dolomitization during penecontemporaneous and shallow burial stage, and burial dolomitization in later stage, are conducive to the preservation of primary pores and development of secondary pores. (4) Multi-stages of dissolution also have strong influence on the development of secondary pores; the secondary transgression and regression cycles during the contemporaneous-penecontemporaneous stage led to exposure and dissolution of soluble minerals and thus the generation of secondary pores. (5) In the burial stage, reservoir pores were further improved due to organic acid dissolution and the dissolution by hydrosulphuric acid from thermochemical sulfate reduction (TSR) and its product H2S. (6) High H2S concentration area in pre-salt reservoirs can thus be considered as targets for future exploration.